2012
DOI: 10.1007/s11904-012-0120-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Latent Tuberculosis Infection in HIV: Shorter or Longer?

Abstract: Nine months of daily isoniazid is efficacious in treating latent M. tuberculosis infection, but completion rates are low, limiting treatment effectiveness. In 2011, three important studies were published involving novel regimens for the treatment of latent M. tuberculosis infection. At least 36 months of isoniazid was more effective than 6 months of isoniazid in one study, but not in another—both of which were conducted among tuberculin skin test positive HIV-infected adults living in high tuberculosis inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Studies conducted concerning this problem do not equivocally show which method of administration of isoniazid is best in considering time. Directly observed 3-month administration once a week of isoniazid plus rifampicin, was at least as effective as a 9-month daily administration of isoniazid, mainly in patients not infected with HIV, and living in countries with low or mediocre morbidity due to tuberculosis [9]. Own study indicated that a centralised time of administration of isoniazid (6 months) was very effective.…”
Section: Discussionmentioning
confidence: 94%
“…Studies conducted concerning this problem do not equivocally show which method of administration of isoniazid is best in considering time. Directly observed 3-month administration once a week of isoniazid plus rifampicin, was at least as effective as a 9-month daily administration of isoniazid, mainly in patients not infected with HIV, and living in countries with low or mediocre morbidity due to tuberculosis [9]. Own study indicated that a centralised time of administration of isoniazid (6 months) was very effective.…”
Section: Discussionmentioning
confidence: 94%
“…Other drugs such as vedolizumab and certolizumab demand more time and even a higher number of patients to have information robust enough to make this kind of correlation. These data are unprecedented in Brazil and show the importance of the request of screening tests for latent tuberculosis over the years and have an increasing observation according to the time of use, since we are facing a high-risk country for this disease, although the disease has low mortality (32)(33)(34)(35)(36) .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with latent TB infections should be treated prior to starting any immune suppressive regimen. It is also important to test for HIV since this may have treatment implications [11]. …”
Section: Discussionmentioning
confidence: 99%